2010
DOI: 10.1007/s00284-010-9816-x
|View full text |Cite
|
Sign up to set email alerts
|

Lactose-Enhanced Cellulase Production by Microbacterium sp. Isolated from Fecal Matter of Zebra (Equus zebra)

Abstract: A cellulase-producing bacterial strain designated Z5 was isolated from the fecal matter of Zebra (Equus zebra). The strain was identified as Microbacterium sp. on the basis of 16S rDNA sequence analysis. The effect of substrates like CMC, avicel, starch, maltose, sucrose, glucose, fructose, galactose, and lactose on cellulase production was also determined. Lactose as the sole carbon source induced cellulase production in this bacterial strain and a positive synergistic effect of lactose and CMC was also obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 24 publications
3
11
0
Order By: Relevance
“…This result indicated that Lactose synergistically enhanced the cellulase synthesis. Similar results reported earlier with a fungus Hypocrea jecorina [37] and in bacteria Microbacterium [21]. However, the lase synthesis cannot be induced by galactose or glucose individually ( Table 1).…”
Section: Effect Of Lactose On Cellulase Productionsupporting
confidence: 77%
See 1 more Smart Citation
“…This result indicated that Lactose synergistically enhanced the cellulase synthesis. Similar results reported earlier with a fungus Hypocrea jecorina [37] and in bacteria Microbacterium [21]. However, the lase synthesis cannot be induced by galactose or glucose individually ( Table 1).…”
Section: Effect Of Lactose On Cellulase Productionsupporting
confidence: 77%
“…Reports from literature suggested that glucose inhibited cellulase synthesis [38] and lactose induces significantly higher cellulase levels than D-galactose in T. reesei [39]. The induction mechanism of cellulase formation is studied in fungus by many workers [40] and in bacteria [21]. We therefore consider that lactose is a water soluble disaccharide in the mixed medium with CMC and was fast taken up by Bacillus sp.…”
Section: Effect Of Lactose On Cellulase Productionmentioning
confidence: 99%
“…BRC1 and BRC2 (Chellapandi and Himanshu, 2008), A. flavithermus EHP1 (Ibrahim and Ahmed, 2007), Microbacterium sp. (Sadhu et al, 2011), Bacillus sp. (Sadhu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…(Chellapandi and Himanshu, 2008), Thermomonospora (George et al, 2001), Microbacterium sp. (Sadhu et al, 2011), Streptomyces transformant T3-1 (Jang and Chen, 2003), Streptomyces sp. F2621 (Tuncer et al, 2004), Clostridium papyrosolvens (Thirumale et al, 2001), Acidothermus cellulolyticus (Shiang et al, 1991), Bacillus sp.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers also reported the maximum CMCase production by using lactose as a source of carbon by Microbacterium sp. [45], Aspergillus hortai [46] and Trichoderma reesei [47]. …”
Section: Effect Of Different Carbon Sources In Culture Medium During mentioning
confidence: 99%